A qualitative analysis of participants' reflections on body image during participation in a randomized controlled trial of acceptance and commitment therapy. Issue 1 (December 2016) - Fogelkvist, Maria; Parling, Thomas; Kjellin, Lars; Gustafsson, Sanna
Abstract Background Negative body image is a risk factor for development and relapse in eating disorders (ED). Many patients continue to be dissatisfied with their body shape or weight after treatment. This study presents a qualitative analysis of written reflections on body image from patients with an ED and a negative body image before and after an Acceptance and Commitment Therapy group treatment at a specialized ED-unit. Method Before and after the treatment participants (n = 47) answered a questionnaire with open ended questions on their thoughts on body image. Data were analyzed through conventional content analysis. Results Body image meant different things for different participants. For some it had to do with how you evaluate your body, whereas others focused on whether their body image was realistic or not. Some emphasized their relationship with their body, while some described body image as strongly related to global self-esteem. These different views on the concept of body image affected the participants' descriptions of their own body image, and how they wanted it to change. Body image was considered a state that fluctuated from day to day. After treatment the participants described changes in their body image, for instance perceiving oneself as less judgmental towards one's body, and a shift in focus to the important things in life. Conclusions The participants had different views on body image and how they wished it to change. Thus treatment interventions targeting negative body image needs to address various aspects of this complex construct. Trial registration This study is part of an RCT registered 02/06/2014 in Clinical Trials, registration number:NCT02058121 .